Who Is to Blame for the Decline of Large Housing Estates? An Exploration of Socio-Demographic and Ethnic Change. - Bolt, Gideon (Springer Open, 2018)
In the 1960s and 1970s, all over Europe housing estates emerged that were very similar with respect to construction methods and urban design. At the same time, housing estates across Europe did not all follow the same trajectory after their completion. This divergence occurred because the main reasons for their deterioration and social degradation are exogenous factors, not internal factors. Of course, it makes a difference whether the physical quality of the dwellings was good and whether the spatial planning was adequate. But even well-designed housing estates are subject to social degradation due to competition with newer neighbourhoods that are usually added at the top of the market and more geared to contemporary housing preferences. In Western Europe, this process of relative depreciation is further exacerbated by the prioritisation of owner-occupation leading to residualisation of the social rented sector. The social and ethnic transformation of large housing estates is not only the consequence of planning and housing policies but also of external factors like immigration and economic decline. Most European countries have witnessed a substantial inflow of immigrants in the previous decades, and many of these find their way to large housing estates. Next to that, the social decline of housing estates is often related to a shrinking local economy. Policies aimed at reversing the decline hurt the sitting population more often than it helped them.
Keywords: Wohnungswesen; Stadtentwicklung; Segregation; Wohnumfeld; Wohnungspolitik